2004
DOI: 10.1002/cphc.200400220
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Dynamics in Myoglobin: Calculation of Infrared Spectra for Photodissociated NO

Abstract: We present molecular dynamics simulations of the photodissociated state of MbNO performed at 300 K using a fluctuating charge model for the nitric oxide (NO) ligand. After dissociation, NO is observed to remain mainly in the centre of the distal haem pocket, although some movement towards the primary docking site and the xenon-4 pocket can be seen. We calculate the NO infrared spectrum for the photodissociated ligand within the haem pocket and find a narrow peak in the range 1915-1922 cm(-1). The resulting blu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 50 publications
5
38
0
Order By: Relevance
“…As early as 1937, it was found that a linear relationship exists between H‐bond strength and the shift in the IR H–X stretching frequency, termed the Badger–Bauer rule (Figure ) . The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…As early as 1937, it was found that a linear relationship exists between H‐bond strength and the shift in the IR H–X stretching frequency, termed the Badger–Bauer rule (Figure ) . The qualitative correlation between H‐bond strengths and stretching frequencies has been observed in many chemical systems . Although a single linear relationship does not hold throughout the many diverse types of H‐bonding, satisfactory linear correlations between enthalpy of H‐bond formation, the IR stretching frequency shift, and the X–H bond elongation were found for structurally related compounds …”
Section: Spectroscopic Signatures Of Hyperconjugationmentioning
confidence: 99%
“…FPCs have proved to be useful to describe the electron density as a molecule undergoes conformational changes 34 and to reproduce up to the quadrupole moment in diatomic molecules. 29,49,50 The nuclear charges are a function of the coordinate of interest, which is the CF bond length in the present case. From the electronic structure calculations for the CF-Morse potential described above, nuclear charges are fitted to the electrostatic field.…”
Section: B Intermolecular Interactionsmentioning
confidence: 99%
“…The CHARMM22 forcefield [12] is used for the protein while the NO and O 2 parametrizations are those from previous work [13,14]. The TIP3P model is used for water [15].…”
Section: Atomistic Simulationsmentioning
confidence: 99%